2021
DOI: 10.3390/molecules26092548
|View full text |Cite
|
Sign up to set email alerts
|

Pressurized-Liquid Extraction as an Efficient Method for Valorization of Thymus serpyllum Herbal Dust towards Sustainable Production of Antioxidants

Abstract: The aim of this study was to valorize Thymus serpyllum herbal dust, a particular fraction distinguished as an industrial waste from filter-tea production. Pressurized liquid extraction (PLE) was used with the aim of overcoming certain obstacles of conventional extraction techniques in terms of shortening extraction time, reducing solvent consumption and energy costs, using “green” solvents and obtaining high yield and quality products. In order to optimize PLE of T. serpyllum herbal dust, the preliminary scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Response surface plots of antioxidant activity (ABTS assay) in the investigated vacuum dried sour cherries are given in Figure 2c, where the influence of three investigated parameters can be seen. According to the results obtained by Mrkonjić et al [42], the antioxidant activity of T. serpyllum extracts, obtained by DPPH, FRAP and ABTS assays, varied between 0.2431 and 0.2914 mMTE/g, 0.6726 and 0.935 7mM Fe 2+ /g and 0.4362 and 0.6482 mM TE/g, respectively. Moreover, according to the results of Chen et al [43], FRAP values in the obtained extracts were found to be primarily affected by the solvent-to-sample ratio, and FRAP was also found to be higher at a high level of ultrasonic power and solvent-to-sample ratio.…”
Section: Antioxidant Activity (Dpph Frap and Abts Assay)mentioning
confidence: 89%
See 3 more Smart Citations
“…Response surface plots of antioxidant activity (ABTS assay) in the investigated vacuum dried sour cherries are given in Figure 2c, where the influence of three investigated parameters can be seen. According to the results obtained by Mrkonjić et al [42], the antioxidant activity of T. serpyllum extracts, obtained by DPPH, FRAP and ABTS assays, varied between 0.2431 and 0.2914 mMTE/g, 0.6726 and 0.935 7mM Fe 2+ /g and 0.4362 and 0.6482 mM TE/g, respectively. Moreover, according to the results of Chen et al [43], FRAP values in the obtained extracts were found to be primarily affected by the solvent-to-sample ratio, and FRAP was also found to be higher at a high level of ultrasonic power and solvent-to-sample ratio.…”
Section: Antioxidant Activity (Dpph Frap and Abts Assay)mentioning
confidence: 89%
“…According to the results of the study by Kashyap et al [41], in which the optimization of ultrasound-assisted extraction of polyphenols from Meghalayan cherry fruit was investigated, it was found that the extraction yield of extract from Megalayan cherry fruit was highly influenced by solvent concentration, solvent-to-solid ratio and extraction time, as shown by the regression analysis. The effects of interactions between temperature, extraction time and ethanol concentration were studied in the work of Mrkonjić et al [42], where it was found that the interaction between extraction time and temperature showed a significant effect, while the interaction between ethanol concentration and temperature showed significance (p ≤ 0.01) on yield content in the Thymus serpyllum extracts. The final equation that can predict the behavior of researched UAE of yield content is shown in Table 4.…”
Section: Defining the Influence Of Process Parameters Extraction Process Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Palmieri et al [154], with different conventional methods involving PLE and rapid solid-liquid dynamic extraction, showed that the aforementioned methods obtain better extract yield from T. vulgaris leaves and stems [154]. Subsequently, the extraction of flavones from Thymus residues using these technologies was studied, as seen in the extracts that were rich in flavones derived from steam distillation residues from T. mastichina [155], and the herbal dust and hydrodistillation residue from T. serpyllum and T. vulgaris obtained by PLE, respectively [73,156]. Finally, not many studies have been recently conducted regarding the extraction of flavones from Ocimum species using alternative methods.…”
Section: Alternative Methods (Environmentally Friendly)mentioning
confidence: 99%